Associations of insomnia symptoms with sociodemographic, clinical, and lifestyle factors in persons with HF: Health and retirement study. Issue 3 (27th January 2022) - Gharzeddine, Rida; McCarthy, Margaret M.; Yu, Gary; Dickson, Victoria V.
Abstract: Insomnia symptoms are very common in persons with heart failure (HF). However, many of the correlates and predictors of insomnia symptoms in this population remain unclear. The purpose of this study is to investigate the associations of sociodemographic, clinical, and lifestyle factors with insomnia symptoms in persons with HF. A theoretical framework was adapted from the neurocognitive model of chronic insomnia to guide the study. Data from the health and retirement study were used for the analysis. Parametric and nonparametric bivariate and multivariate analyses were conducted to investigate these associations. Age, depressive symptoms, comorbidity, dyspnea, pain, and smoking had significant bivariate associations with all insomnia symptoms. Race, Hispanic ethnicity, marital status, household income, poverty, and physical activity were associated with difficulty initiating sleep (DIS) and early morning awakening (EMA). Female sex, education, and alcohol consumption had a significant bivariate association with DIS. Sleep‐disordered breathing and body mass index were significantly associated with EMA. Multivariate analysis suggested that depressive symptoms, comorbidity, dyspnea, and pain had independent associations with each insomnia symptom. Age explained DIS and difficulty maintaining sleep, and significant interaction effects between age and physical activity on DIS and EMA were revealed. Results suggest that insomnia symptoms are associated with several sociodemographic, clinical, and lifestyle factors. Age below 70 years, depressive symptoms, comorbidity, dyspnea, and pain might be considered as a phenotype to identify persons with HF who are at increased risk for insomnia symptoms.